X-Ray Diffraction and X-Ray Photoelectron Spectroscopy Characterization of Maleic Anhydride-Grafted Ethylene-Propylene-diene Terpolymer Based Thermoplastic Elastomers - Kim1, Yeowool; Kwon1, Hyuk-Min; Choi1, Sung-Seen; Woo Bae2, Jong; Kim2, Jung-Soo (Asian Journal of Chemistry, 2013)
Maleic anhydride-grafted ethylene-propylene-diene terpolymer (MAH-g-EPDM) based thermoplastic elastomers were characterized by X-ray diffraction and X-ray photoelectron spectroscopy. The analysis focused on the formation of ionomers between MAH-g-EPDM and zinc oxide. The X-ray diffraction patterns of the thermoplastic elastomers showed different peak intensities of zinc oxide according to the formulations. The X-ray photoelectron spectroscopy spectra of the thermoplastic elastomers showed a shift in the binding energies of carbon and oxygen atoms. The degree of ionomer formation was estimated from percentage crystallinity determined by the XRD patterns and from difference in the relative intensities of the C1s and O1s peaks in the X-ray photoelectron spectroscopy spectra.